PENEGAKAN HUKUM TINDAK PIDANA PENYALAHGUNAAN BAHAN BAKAR MINYAK BERSUBSIDI JENIS SOLAR BERDASARKAN UNDANG UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK BUMI DAN GAS DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Putra, Ariadi Mandala; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
important function in provision of indrustial fuel ,household, and basic needs in our life. Industrial activities with product be produced by a company which thrive of industrial technology and transportationneed more crude oil and gas. Rule and cntrol of this case is very important for create a healthy market needs. Types of research used in this study is the author of sosiological legal research. This case study as as businesses look at the effect of the enactement of positive law on people lives and further and according to the laws or regulations applicable to analyzing the problem in the opinion of legal sources in the real live. This research was conducted at the Police Station PekanbaruResort Town, Prosecutor Pekanbaru and Court of Pekanbaru. The data used is primary data, secondary data, and tertiary data, technique of colleting data using questionnaires, interviews, literature stdy and observation The conclusion of the research are, first law enforcement criminal offense of abuse of subsidized fuel oil diesel with the actions of the police are preventive measures. Second obstacles encountered in law enforcement by police is the lack of quality human resources, means and inadequate infrastructure also the dufficulty of revealing evidence. Third efforts to overcome barriers to learning activitiesare organized spesifically for the police, complementing the existing infrastructure, fostering family relationshis with the community, and so on.Keywords: Criminal Offense-Fuel-Diesel Fuel